Prevalence and risk factors of metabolic syndrome in obese children and adolescents: the role of the severity of obesity - Sen, Yasar; Kandemir, Nurgun; Alikasifoglu, Ayfer; Gonc, Nazli; Ozon, Alev (Springer, 2008)
The present study was performed to determine the prevalence of metabolic syndrome (MS) and its risk factors in obese children and adolescents. The study included 352 obese children and adolescents (body mass index [BMI]>= 95th percentile) aged between 2 and 19 years. The diagnosis of MS was made according to the criteria adapted from the World Health Organization (WHO) and the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) guidelines. BMI z-scores were calculated to assess the degree of obesity. The prevalence of MS and risk factors were determined. Determinants of MS were examined using regression analysis. The prevalence of MS was 41.8%. The age at onset of obesity, sedentary life-span, fasting blood levels of glucose, insulin, triglyceride, very-low-density lipoprotein (VLDL) cholesterol, and alanine aminotransferase (ALT) were higher, while levels of high-density lipoprotein (HDL) cholesterol and the number of actively spent hours were lower in cases with MS (p < 0.05). The most important determinant of MS was BMI z-score (r=0.31, p < 0.0001). A one-point increase in BMI z-score yielded a 2-fold increase in the prevalence of MS. The prevalence of MS increased from 27.6% to 60.7% when the BMI z-score increased from 2.3 to 3.3. The risk of developing MS was 2.6-fold higher in cases with BMI z-score > 3 when compared to those with z-scores between 2 and 3. The results from this study indicate that, although the correlation between MS and the BMI z-score was weak, the BMI z-score may be an effective parameter in identifying obese children and adolescents at risk for MS. Screening the cases with BMI z-scores >= 2 for MS is important for establishing an early diagnosis.
Keywords: childhood obesity; BMI z-score; metabolic syndrome; type 2 diabetes mellitus; cardiovascular risk factors